Strategic Management - Reed, Kennedy B. (Open textbook library., 2020)
STRATEGIC MANAGEMENT offers an introduction to the key topics and themes of strategic management. The authors draw on examples of familiar companies and personalities to illustrate the different strategies used by today’s firms—and how they go about implementing those strategies. Students will learn how to conduct a case analysis, measure organizational performance, and conduct external and internal analyses. In short, they will understand how organizations operate at the strategic level to be successful. An older version of Mastering Strategic Management (2015) by University of Minnesota Libraries Publishing can be found here: https://open.lib.umn.edu/strategicmanagement/